Cosmogenic effects on chromium isotopes in meteorites. (15th April 2019) - Liu, Jia; Qin, Liping; Xia, Jiuxing; Carlson, Richard W.; Leya, Ingo; Dauphas, Nicolas; He, Yongsheng
Abstract: The 53 Mn- 53 Cr short-lived radionuclide decay system is a powerful tool to investigate the timescales of early solar system processes. A complication arises, however, from the fact that spallation and thermal/epithermal neutron capture processes induced by cosmic rays can significantly alter 53 Cr/ 52 Cr ratios in solar system objects that have long exposure ages and high Fe/Cr ratios. Quantifying these cosmogenic effects helps constrain the cosmic ray exposure history of extraterrestrial samples. The isotopic shifts produced by cosmic ray irradiation also need to be corrected before the Cr isotope systematics can be used as a dating tool and as a tracer of nucleosynthetic provenance. To investigate the impact of cosmogenic production on Cr, the Cr isotopic compositions of 25 samples from 16 iron meteorites belonging to nine different chemical groups were measured. The measurements show that exposure to cosmic rays can cause large coupled excesses in ε 53 Cr (up to +268.29 ± 0.14; 2SE) and ε 54 Cr (up to +1053.78 ± 0.72; 2SE) with a best fit line of ε 54 Cr = (3.90 ± 0.03) × ε 53 Cr. The magnitude of Cr isotope production is controlled by various factors including the exposure age, the chemical composition (i.e ., Cr concentration and Ni/Fe ratio) and shielding conditions. Nevertheless, the correlation of ε 53 Cr and ε 54 Cr is independent of these factors, which provides an effective method to evaluate the cosmogenic contribution to 53 Cr by monitoring the cosmogenic variations in ε 54 Cr in meteoritic irons. The results are compared with modeling results that yield a slightly shallower slope of 3.6 ± 0.2. Modeling results for the olivine in stony meteorites yield a higher slope (∼5.4). However, the previous estimated results for lunar samples (stony targets for comic ray irradiation) exhibit an observably shallower slope (∼2.62). The reason for the different slopes is that the production rates of different cosmogenic Cr isotopes in iron meteorites and lunar samples are in different proportions. The differences may not be completely controlled by the higher thermal and epithermal neutron fluencies in lunar samples than in iron meteorites, but instead may largely reflect different radiation geometry between the two. More studies are needed to solve this open question.